Changes in bioactive compounds in spiny coriander leaves in response to inflorescence pruning at different growth stages - Campos, Renê A.S.; Seabra Junior, Santino; Gonçalves, Gabriela G. [UNESP]; Neves, Leonarda Grillo; de Gusmão, Sérgio A.L.; Vianello, Fábio; Lima, Giuseppina P.P. [UNESP] (Elsevier, 2019)
The objective of the study was to evaluate the effect of inflorescence pruning on spiny coriander and determine the levels of antioxidants at different growth stages. Inflorescence pruning increased leaf biomass by 188%, although total biomass did not vary among treatments. Pruning altered the biomass partition, induced the earmarking of a higher percentage of photosynthates for the production of new leaves, and increased the leaf contents of reducing sugars, sucrose and soluble proteins. The contents of bioactive compounds and antioxidant activity were not affected by inflorescence pruning. Regarding the growth stages, the polyphenol and flavonoid contents were high during the juvenile stage, and highest levels of carotenoids, chlorophyll a and chlorophyll b were produced at the beginning of plant maturation. From the full maturity stage onwards, peroxidase (POD) and polyphenoloxidase (PPO) were highest, coinciding with a decrease in bioactive compounds. Considering the production of bioactive compounds and antioxidant, POD and PPO activities, the ideal harvesting time would be in the late juvenile and early maturation stages of spiny coriander, between 90 and 120 days after germination. Moreover, inflorescence pruning is recommendable for spiny coriander cultivation, for increasing the leaf biomass without affecting the leaf levels of bioactive compounds and antioxidant activity. Our results highlight the relevance of the growth stages for the production of bioactive compounds of this crop, contributing to improve the cultivation practices, with higher yields and an optimized use of the therapeutic properties of the leaves.
Keywords: Antioxidants; Eryngium foetidum L.; Growth; Inflorescence pruning; Partitioning; POD; PPO